In search of the Mexican Beverly Hills : Latino suburbanization in postwar Los Angeles - Gonzalez, Jerry, 1978- (New Brunswick, New Jersey : Rutgers University Press, 2018)
"Residential and industrial sprawl changed more than the political landscape of postwar Los Angeles. It expanded the employment and living opportunities for millions of Angelinos into new suburbs. In Search of the Mexican Beverly Hills examines the struggle for inclusion into this exclusive world--a multilayered process by which Mexican Americans moved out of the barrios and emerged as a majority population in the San Gabriel Valley--and the impact that movement had on collective racial and class identity. Contrary to the assimilation processes experienced by most Euro-Americans, Mexican Americans did not graduate to whiteness on the basis of their suburban residence. Rather, In Search of the Mexican Beverly Hills illuminates how Mexican American racial and class identity were both reinforced by and took on added metropolitan and transnational dimensions in the city during the second half of the twentieth century"--
Frontmatter -- Contents -- Introduction -- 1. The Lands Of Mañana -- 2. Mexican Americans And The Suburban Ideal -- 3. El MAPA To The Suburban Ideal -- 4. Suburban Renewal -- Epilogue: Let'S Take A Trip . . . -- Acknowledgments -- Notes -- Index -- About The Author
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 02, 2018).
JSTOR
Keywords: Mexican Americans -- California -- Los Angeles Suburban Area; Los Angeles Suburban Area (Calif.) -- History; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; HISTORY -- United States -- State & Local -- West (AK, CA, CO, HI, ID, MT, NV, UT, WY); POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; SOCIAL SCIENCE -- Sociology -- Urban; HISTORY -- United States -- 20th Century; SOCIAL SCIENCE -- Social Classes; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Mexican Americans; California -- Los Angeles Suburban Area; History